Simulation test for impartment of use-dependent plasticity by inactivation of axonal potassium channels on hippocampal mossy fibers - Zheng, Fumeng; Kamiya, Haruyuki (Frontiers in Cellular Neuroscience, 2023)
Modification of axonal excitability directly impacts information transfer through the neuronal networks in the brain. However, the functional significance of modulation of axonal excitability by the preceding neuronal activity largely remains elusive. One remarkable exception is the activity-dependent broadening of action potential (AP) propagating along the hippocampal mossy fibers. The duration of AP is progressively prolonged during repetitive stimuli and facilitated presynaptic Ca2+ entry and subsequent transmitter release. As an underlying mechanism, accumulated inactivation of axonal K+ channels during AP train has been postulated. Since the inactivation of axonal K+ channels proceeds on a time scale of several tens of milliseconds slower than the millisecond scale of AP, the contribution of K+ channel inactivation in AP broadening needs to be tested and evaluated quantitatively. Using the computer simulation approach, this study aimed to explore the effects of the removal of the inactivation process of axonal K+ channels in the simple but sufficiently realistic model of hippocampal mossy fibers and found that the use-dependent AP broadening was completely abolished in the model replaced with non-inactivating K+ channels. The results demonstrated the critical roles of K+ channel inactivation in the activity-dependent regulation of axonal excitability during repetitive action potentials, which critically imparts additional mechanisms for robust use-dependent short-term plasticity characteristics for this particular synapse.